L’exploitation d’outils d’observation et d’évaluation élaborés pour les discussions asynchrones dans l’enseignement de l’expression argumentative en langue étrangère. Use of observation and evaluation tools elaborated for online discussions in teaching and learning argumentative tasks. - Górecka, Joanna (Glottodidactica, 2016)
The main problem of the paper is if tools elaborated to observe and evaluate online discussion tasks can be also applied in face-to-face context and b-learning scenarios. I will discuss the main features of those tools (Henri 1992; Gunawardena et al. 1997; Garrison et al. 2001; Newman et al. 1995; Wozniak et Silveira 2004) and focus specifically on those features which allow the negotiation of the aims and the course of the argumentative, thus inviting critical argumentation.